Perception of emotion and postural stability control at different distances - Chikh, Soufien; Charrada, Salma; Watelain, Eric (Journal of eye movement research, 2022)
The effect of emotion on postural control has been widely demonstrated in the literature. Postural control also depends on the distance that separates the subject from the observed stimulus. This work examines (i) the effect of distance on the perception of emotional stimuli and (ii) its effect on postural control. Sixty-eight women were asked to maintain orthostatic equilibrium under three emotional conditions (positive, negative, and neutral) at four distances (0.5 m, 2.1 m, 6 m, and 10 m). The findings showed that the perception of emotions was not influenced by distance but was influenced by valence and intensity, and that postural control was not influenced by emotional valence but by distance, with reduced oscillation amplitudes at 0.5 m distance. The perception of the image (valence and intensity) depended on the content, but not on the distance, and the presentation of emotional images tended to activate the defensive system, regardless of the emotional content. The center of pressure sway amplitude increased with an eye–object distance of up to 6 m (role of vision). The perception of the emotional effect was not linked to the distance effect on the postural control of women in static positions.